Answer:
Circle B:
![(x+4)^2+(y+3)^2=4](https://img.qammunity.org/2021/formulas/mathematics/high-school/twrhgw33gsk7q82fgm2amxk3vd8j512bf7.png)
Circle F:
![(x-4)^2+(y-1)^2=16](https://img.qammunity.org/2021/formulas/mathematics/high-school/1jutev9u1jyk7im8erujlf6m427w1dq47x.png)
Explanation:
We can write the equation of a circle equation with center on (h,k) and radius r as:
![(x-h)^2+(y-k)^2=r^2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/3gezmntbbjw0kxpks4y5gde90ue9dh956u.png)
Then, we analyze the circle will have for the circle B:
- It has a center in x=-4 and y=-3.
- It radius can be calculated from the distance from the center (x,y)=(-4,-3) to one of its points (x,y)=(-4, -1). Then, its radius is r=2.
Then, we can write the equation as:
![(x-h)^2+(y-k)^2=r^2\\\\h=-4\\k=-3\\r=2\\\\(x+4)^2+(y+3)^2=4](https://img.qammunity.org/2021/formulas/mathematics/high-school/7t9y67c1h9nzktoycjletteoqwwlvruk9l.png)
we analyze the circle will have for the circle F:
- It has a center in x=4 and y=1.
- It radius can be calculated from the distance from the center (x,y)=(4, 1) to one of its points (x,y)=(0, 1). Then, its radius is r=4.
Then, we can write the equation as:
![(x-h)^2+(y-k)^2=r^2\\\\h=4\\k=1\\r=4\\\\(x-4)^2+(y-1)^2=16](https://img.qammunity.org/2021/formulas/mathematics/high-school/vfk1eneq22pu3bxu029u88puam1zt4btnn.png)